2018
DOI: 10.1017/s0031182018000689
|View full text |Cite
|
Sign up to set email alerts
|

In vitroovicidal and larvicidal activities of some saponins and flavonoids against parasitic nematodes of goats

Abstract: This study assessed the anthelmintic activity of plant-derived compounds against gastrointestinal nematodes of goats using the egg hatch and larval motility assays. The compounds tested were saponins (digitonin and aescin) and their respective sapogenins (aglycones), hecogenin acetate and flavonoids (catechin, hesperidin, isocordoin and a mixture of isocordoin and cordoin). Additionally, cytotoxicity of active substances was analysed on Vero cell through 3-4,5-dimethylthiazol-2-yl,2,5diphenyltetrazolium bromid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…These results agree with the previous findings regarding the anthelmintic effect of grape pomace extract against GINs [48]. Coriander oil and linalool, are reported to affect membrane diffusion through alteration of electrostatic property and permeability of cuticle in addition to inhibition of cuticular protein [49,50]. Therefore, the cytotoxicity of combined coriander oil and linalool on MDCK cells observed at > 1% concentration may be attributed to disruption of cell membrane integrity.…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with the previous findings regarding the anthelmintic effect of grape pomace extract against GINs [48]. Coriander oil and linalool, are reported to affect membrane diffusion through alteration of electrostatic property and permeability of cuticle in addition to inhibition of cuticular protein [49,50]. Therefore, the cytotoxicity of combined coriander oil and linalool on MDCK cells observed at > 1% concentration may be attributed to disruption of cell membrane integrity.…”
Section: Discussionsupporting
confidence: 92%
“…The egg hatch test (EHT) is a standard bioassay commonly used for the in vitro screening of the anthelmintic properties of natural compounds against gastrointestinal nematodes [11,12]. EHT is in fact considered a valid and useful test for the evaluation of the in vitro efficacy of drugs and one of the main in vitro methods used for the detection of benzimidazole resistance in nematode parasites [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Among plant-derived substances, saponins are considered as potential anthelmintic natural compounds [11,12]. Biological effects of saponins are normally ascribed to their specific interaction with cell membranes [15], causing changes in cell permeability.…”
Section: Introductionmentioning
confidence: 99%
“…The available data from literature also confirm the 'in vitro' anthelmintic activity of this class of compounds against ruminant GIS. The saponins aescin and digitonin [17] and saponin fractions contained in Zizyphus joazeiro [16], Phytolacca icosandra [34] and Agave sisalana [18] showed 'in vitro' ovicidal activity against the nematodes of small ruminants. Similarly, the 'in vitro' ovicidal action of Combretum molle against eggs of H. contortus from sheep and of Ipomoea chiliantha, Tocoiena formosa and Aspilia latissima against the eggs of Haemonchus placei from cattle, have been attributed to their saponin content [33,35].…”
Section: Discussionmentioning
confidence: 99%
“…The anthelmintic activity of these plant extracts is related to the presence of biologically active metabolites such as condensed tannins, flavonoids, steroids, terpenoids, alkaloids and saponins [14,15]. Among these, saponins are important secondary metabolites from plants, and are considered as potential anthelmintic natural compounds [16,17]. It is reported that fractions rich in steroidal and triterpenic saponins from Agave sisalana have an 'in vitro' ovicidal effect against the nematodes of goats [18].…”
Section: Introductionmentioning
confidence: 99%